EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DENGAN STRATEGI PETA KONSEP DITINJAU DARI KECERDASAN SPASIAL SISWA - Westi Bilda; Mardiyana Mardiyana; Gatut Iswahyudi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from the spatial intelligence students. The type of this research was a quasi-experimental research. The population was the students of the VIII class of MTsN Ngawi Regency in the academic year of 2013/2014. The samples of the research consisted of 314 students and were taken through stratified cluster random sampling. Instruments used were spatial intelligence test and mathematics achievement test. The proposed hypothesis of the research were tested by using the unbalanced two-way analysis of variance. The conclusions of this research were as follows. 1) NHT and mind concept gives better mathematics achievement than NHT model and direct learning model, and NHT model gives the same mathematics achievement as direct learning. 2) The high spatial intelligence students have better mathematics achievement than midlle and low spatial intelligence students, midlle spatial intelligence students have better mathematics achievement than low spatial intelligence students, 3) For NHT and mind concept and NHT, students having high, moderate and low spatial intelligence have the same achievement. For direct learning model, students having high spatial intelligence had better achievement than students having moderate and low, then, students having moderate spatial intelligence have better achievement than students having low spatial intelligence. 4) For students having high and moderate spatial intelligence NHT and mind mapping concept model, NHT and direct instructionl model have the same effect toward students’ achievement. For students having low spatial intelligence, NHT and mind concept gives better learning achievement than NHT. NHT gives better learning achievement than direct learning model. NHT gives the same learning achievement as direct learning model.Keywords: NHT, mind mapping concept, spatial intelligence.